Control of angiogenesis by galectins involves the release of platelet-derived proangiogenic factors - Etulain, Julia (2014)
Platelets contribute to vessel formation through the release of angiogenesis-modulating factors stored in their α-granules. Galectins, a family of lectins that bind β-galactoside residues, are up-regulated in inflammatory and cancerous tissues, trigger platelet activation and mediate vascularization processes. Here we aimed to elucidate whether the release of platelet-derived proangiogenic molecules could represent an alternative mechanism through which galectins promote neovascularization. We show that different members of the galectin family can selectively regulate the release of angiogenic molecules by human platelets. Whereas Galectin (Gal)-1, -3, and -8 triggered vascular endothelial growth factor (VEGF) release, only Gal-8 induced endostatin secretion. Release of VEGF induced by Gal-8 was partially prevented by COX-1, PKC, p38 and Src kinases inhibitors, whereas Gal-1-induced VEGF secretion was inhibited by PKC and ERK blockade, and Gal-3 triggered VEGF release selectively through a PKC-dependent pathway. Regarding endostatin, Gal-8 failed to stimulate its release in the presence of PKC, Src and ERK inhibitors, whereas aspirin or p38 inhibitor had no effect on endostatin release. Despite VEGF or endostatin secretion, platelet releasates generated by stimulation with each galectin stimulated angiogenic responses in vitro including endothelial cell proliferation and tubulogenesis. The platelet angiogenic activity was independent of VEGF and was attributed to the concerted action of other proangiogenic molecules distinctly released by each galectin. Thus, secretion of platelet-derived angiogenic molecules may represent an alternative mechanism by which galectins promote angiogenic responses and its selective blockade may lead to the development of therapeutic strategies for angiogenesis-related diseases.